Research on the Disruptive Innovation of NEV to the Traditional Automotive Industry from the Perspective of Business Models - Huang, Yutong (Exploring Science Academic Conference Series, 2026)
Since its formal proposal, disruptive innovation theory has undergone more than two decades of improvement and evolution, exerting a profound influence on academic fields such as business and enterprise management. As the market share of New Energy Vehicles (NEVs) has gradually increased in recent years, people have noticed that traditional fuel vehicle enterprises seem to be struggling to cope with the pressure from new car-making forces. To analyze the mechanism of the dual drive of “technology + business model” and break through the transformation predicament of traditional automakers, this paper, relying on the disruptive innovation theory refined and expounded by Christensen in 2015, adopts methods such as systematic literature retrieval, case analysis, and comparative study, and selects typical international automakers such as Tesla, BYD, and Volkswagen as cases. Through conducting specific case studies on traditional energy and NEV enterprises worldwide, the author has distilled the intrinsic mechanisms of disruptive innovation and the development of the automotive industry, and then put forward breakthrough viewpoints. Research shows that the emergence of NEV represents a disruptive innovation for traditional automakers not only in terms of products but also in the entire business system. This makes it difficult for the decades of business models and management experience of traditional automakers to match the development logic of the new energy vehicle industry, and their long-accumulated business model advantages and management experience have been gradually weakened.